Recent advances in the synthesis of five‐ and six‐membered heterocycles as bioactive skeleton: A concise overview. Issue 6 (8th February 2022) - Jangir, Nidhi; Poonam,; Dhadda, Surbhi; Jangid, Dinesh K.
Abstract: Heterocyclic compounds play a tremendous role in the field of medicinal chemistry due to their association with diverse pharmacological properties. Most of the pharmaceutical drugs used in medicines possess a wide range of heterocyclic nucleus. It was decided basis on literature studies that various synthetic protocols like microwave‐assisted, nanocatalysed, green synthesis, click reaction, and multicomponent routes could be used for the betterment of the purity of products, selectivity, and better yields of the products. We have focused attention on the development of synthetic strategies of the above‐mentioned moieties because N ‐, O ‐ and S ‐ containing heterocyclic compounds have seemed owing to a wide diversity of their biological activities viz . antioxidant, anticancer, anticonvulsant, anti‐inflammatory, neuroprotective, antiproliferative, anti‐obesity, antihyperglycemic, antihypercholesteroler, antiulcer, antidiabetic, antileishmanial, antitrypanosomal, antibiotic, etc . In this review article, an overview of the applications of synthetic protocols for the preparation of five‐membered and six‐membered heterocyclic compounds containing two or more heteroatoms ( O, N, S ) at different‐different positions along with their different potent and competent candidates against various diseases is presented in last 10–15 years. Abstract : The recent developments in the synthetic approaches of N ‐, O ‐ and S ‐ containing heterocyclic compounds include various synthetic procedures like microwave‐assisted, nanocatalysed, green synthesis, click reaction, and multicomponent routes with the reported pharmacologically potent heterocycles of these categories are summarised in this review. This review is further subcategorized based on five‐ and six‐membered heterocycles along with their respective benzofused analogues.